THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON CONSUMER SATISFACTION AND REPURCHASE INTEREST (STUDY AT STARBUCKS) - Aulia Adisti Husnaini Tanjung; Else Else; M. Shultan Satria; Suhail Elvari (Indonesian Marketing Journal, 2022)
This study tested and analyzed product quality, service, customer satisfaction, and consumer repurchase interest at Starbucks Indonesia. The research population sample is Starbucks Indonesia Consumers with a sample size of 105 respondents. In testing the data analysis hypothesis using SPSS Version 21.0, the results show that product quality and service quality significantly affect consumer satisfaction. Product quality and consumer satisfaction affects repurchase intention, but service quality has no significant effect on the repurchase intention.